Application of zahir accounting version 6 for processing accounting data At Mahfud Jaya Perabot Karawang - Siti Nurajizah; Normah Normah; Irlia Oktavianisa (Institute of Computer Science (IOCS), 2023)
The rapid development of the times has brought many benefits to the company. The development of this technology also facilitates the implementation of the company's operational activities. Generally there are three kinds of companies that generate profits such as service companies, trading companies and manufacturing companies. Mahfud Jaya Furniture Store is a company engaged in the trading of furniture or various kinds of household appliances and cleaning equipment. The process of recording accounting data at the Mahfud Jaya Furniture Store still uses a manual system using paper media. The recording process becomes inaccurate and carries more risk of data loss and is very inefficient because it creates piles of files which, if stored for too long, will be damaged and take up space. Therefore the authors conducted research using observation and interview methods. The author collects all data and then performs analysis. Based on the research results, it is interesting for the authors to implement a computerized accounting data processing program using accounting software, namely Zahir Accounting Version 6 at the Mahfud Jaya Furniture Store. With the development of this system will minimize the problems that arise and the presentation of information can be done more quickly, precisely and accurately